siRNA inhibition of endocytic pathways to characterize the cellular uptake mechanisms of folate-functionalized glycol chitosan nanogels - Pereira, Paula (2015)
Glycol chitosan nanogels have been widely used in gene, drug, and contrast agent delivery in an effort to improve disease diagnosis and treatment. Herein, we evaluate the internalization mechanisms and intracellular fate of previously described glycol chitosan nanogels decorated with folate to target the folate receptor. Uptake of the folate-decorated nanogel was impaired by free folate, suggesting competitive inhibition and shared internalization mechanisms via the folate receptor. Nanogel uptake was shown to occur mainly through flotillin-1 and Cdc42-dependent endocytosis. This was determined by inhibition of uptake reduction observed upon siRNA depletion of these two proteins and the pathways that they regulate. The data also suggest the involvement of the actin cytoskeleton in nanogel uptake via macropinocytosis. After 7 h of incubation with HeLa cells, approximately half of the nanogel population was localized in endolysosomal compartments, whereas the remaining 50% of the material was in undefined regions of the cytoplasm. Glycol chitosan nanogels may thus have potential as drug delivery vectors for targeting different intracellular compartments.